Repetitive Passive Finger Movement Modulates Primary Somatosensory Cortex Excitability - Sasaki, Ryoki; Tsuiki, Shota; Miyaguchi, Shota; Kojima, Sho; Saito, Kei; Inukai, Yasuto; Otsuru, Naofumi; Onishi, Hideaki (Frontiers in Human Neuroscience, 2018)
Somatosensory inputs induced by repetitive passive movement (RPM) modulate primary motor cortex excitability; however, it is unclear whether RPM affects primary somatosensory cortex (S1) excitability. In this study, we investigated whether RPM affects somatosensory evoked potentials (SEPs) and resting state brain oscillation, including alpha and beta bands, depend on RPM frequency. Nineteen healthy subjects participated in this study, and SEPs elicited by peripheral nerve electrical stimulation were recorded from the C3’ area in order to assess S1 excitability (Exp. 1: n = 15). We focused on prominent SEP components such as N20, P25, and P45-reflecting S1 activities. In addition, resting electroencephalograms were recorded from C3’ area to assess the internal state of the brain network at rest (Exp. 2: n = 15). Passive abduction/adduction of the right index finger was applied for 10 min at frequencies of 0.5, 1.0, 3.0, and 5.0 Hz in Exp. 1, and 1.0, 3.0, and 5.0 Hz in Exp. 2. No changes in N20 or P25 components were observed following RPM. The 3.0 Hz-RPM decreased the P45 component for 20 min (p < 0.05), but otherwise did not affect the P45 component. There was no difference in the alpha and beta bands before and after any RPM; however, a negative correlation was observed between the rate of change of beta power and P45 component at 3.0 Hz-RPM. Our findings indicated that the P45 component changes depending on the RPM frequency, suggesting that somatosensory inputs induced by RPM influences S1 excitability. Additionally, beta power enhancement appears to contribute to the P45 component depression in 3.0 Hz-RPM.